From reading deculture to reading culture - Lalangui Sarango, Ricardo Geovanni; Tinoco Tinoco, Wilson Alcívar; Jaramillo Aguilar, Betty Azucena (SATHIRI, 2021)
The objective of this research is to make visible the alienating effects of reading deculture, as a teacher awareness to appropriate the reading culture, from the pedagogy of praxis. The research approach is mixed, from the point of view of a non-experimental design and a type of bibliograhpic research character, descriptive and field nature. To collect the empirical information, a survey based on a questionnaire of five questions was applied to the entire population of teachers of the Colegio de Bachillerato “Ciudad de Portovelo”, information that allowed to conclude that the respondants show a clear ignorance about what was polled. A 87.5% about the cognition proposed by Vigotsky, a 75% on the context of reading deculture, a 95.83% on reading culture or cultural practice, 100% on the context of appropriation and a 91.67 % referring to praxis by Freire. This evidences that educators do not have enough conceptual and methodological training regarding their pedagogical praxis expected to promote cultural reading in students. Therefore, it is necessary to recommend this study to be socialized among teachers, so that they become conscious of the negative effects of reading deculture on pupils and appropriate of reading culture guidelines, from situated cognition, appropriation and praxis as transformative social exercise.